Additivity of standardized ileal digestibility of amino acids in mixed diets containing multiple protein sources for growing pigs fed three crude protein levels. Issue 4 (29th April 2018) - Liu, Z.; Liu, J.; Chen, L.; Lv, S.; Liu, L.; Tang, X.; Zhang, H.
Summary: This study was conducted to investigate the effect of dietary crude protein (CP) levels of semi‐purified diets on the additivity of values for standardized ileal digestibility (SID) of amino acids (AA) in mixed diets from multiple protein sources for growing pigs. A total of 28 barrows (initial BW, 66.4 ± 1.3 kg) were surgically fitted with simple T‐cannulas at the distal ileum and assigned to a replicated 14 × 4 incomplete Latin square design with 14 diets and 4 periods. The 14 experimental diets consisted of a nitrogen‐free diet; a corn‐based diet (80 g CP/kg); nine semi‐purified diets containing soya bean meal (SBM), canola meal (CM) or corn distillers dried grains with solubles (cDDGS), each type (protein source) of semi‐purified diets supplied 80, 120 or 160 g CP/kg, respectively; three mixed diets based on corn, SBM, CM and cDDGS formulated to contain 120, 160 and 200 g CP/kg respectively. Pigs were fed each of the 14 diets during a seven‐day period, and ileal digesta were collected from 08:00 a.m to 6:00 p.m on day 6 and 7. Chromic oxide was added as an indigestible marker. Results indicated that the SID of CP and AA were not affected by CP levels ( p > .05). Values for SID of AA were additive ( p > .05) with the exception of His and Lys; Arg and Lys; Arg, Lys, Thr, Asp, Cys and Gly in the mixed diets containing 120, 160 and 200 g CP/kg respectively ( p < .05). In conclusion, additivity of SID values of AA in the mixed diets at different CP levels was not affected by the CP levels of semi‐purified diets for growing pigs. Therefore, it is recommended that SID values of AA should be used to formulate practical diets containing multiple ingredients for pigs.